UNDERSTANDING GEN Z INVESTMENT DECISIONS: CAPITAL MARKET LITERACY AND EMOTIONAL BIASES - Rohmad Fuad Armansyah; Herwin Ardianto; Chitra Laksmi Rithmaya (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2023)
This study aimed to advance behavioral economics, specifically behavioral finance bias and literacy, in Generation Z investment decisions. The research data used 389 Generation Z capital market investors who were members of the investor community group. The data analysis technique used the PLS-SEM approach. The study's results revealed that capital market literacy, overconfidence bias, confirmation bias, and fear of better options wielded substantial influence over the investment decisions made by Generation Z individuals within the Indonesian capital market. Interestingly, it was observed that mental accounting exhibited an insignificant effect on these investment choices. These empirical insights not only enhanced comprehension of investors' financial behaviors within the capital market but also offered valuable insights to stakeholders in the capital market ecosystem, aiding them in comprehending and addressing the behavioral biases inherent in the decisions of capital market investors.